GEOTHERMAL REGIME AND GENESIS OF THE NINETY-EAST AND CHAGOS-LACCADIVE RIDGES - Verzhbitsky E.V. (My University, 2003)
There are two well-founded hypotheses of the Ninety-East and Chagos-Laccadive Ridges genesis: the hypothesis of the extrusive source disposed at a junction of the spreading axis with transform fault and the hot spot hypothesis. The northward increasing trend of volcanism age and the average formation rate of the ridges calculated from the present deep sea drilling data (9 cm/a) shows their common genesis. Their origin is related to a northward migration of the Indian plate during the Late Cretaceous and Paleogene, with an average rate of 9 cm/a. The features of the age variations along the axes of the Ninety-East and Chagos-Laccadive ridges prove the relation of basement subsidence to the cooling model of the oceanic lithospheric evolution. Heat flow distribution in the vicinity of the ridges fits the same model of their oceanic origin and affiliation to the Indian plate. Assessment of the geothermal data and the basaltic age relate the origin of the Ninety-East and Chagos-Laccadive ridges to the hot spots hypothesis.